A conserved function of Human DLC3 and Drosophila Cv-c in testis development - Sol Sotillos; Isabel von der Decken; Ivan Domenech Mercadé; Sriraksha Srinivasan; Dmytro Sirokha; Ludmila Livshits; Stefano Vanni; Serge Nef; Anna Biason-Lauber; Daniel Rodríguez Gutiérrez; James Castelli-Gair Hombría (eLife, 2022)
The identification of genes affecting gonad development is essential to understand the mechanisms causing Variations/Differences in Sex Development (DSD). Recently, a DLC3 mutation was associated with male gonadal dysgenesis in 46,XY DSD patients. We have studied the requirement of Cv-c, the Drosophila ortholog of DLC3, in Drosophila gonad development, as well as the functional capacity of DLC3 human variants to rescue cv-c gonad defects. We show that Cv-c is required to maintain testis integrity during fly development. We find that Cv-c and human DLC3 can perform the same function in fly embryos, as flies carrying wild type but not patient DLC3 variations can rescue gonadal dysgenesis, suggesting functional conservation. We also demonstrate that the StART domain mediates Cv-c's function in the male gonad independently from the GAP domain's activity. This work demonstrates a role for DLC3/Cv-c in male gonadogenesis and highlights a novel StART domain mediated function required to organize the gonadal mesoderm and maintain its interaction with the germ cells during testis development.